Special Issue Conclusion - Hannah Bucher; Anne-Kathrin Stroppe; Axel M. Burger; Thorsten Faas; Harald Schoen; Marc Debus; Sigrid Roßteutscher; Denis Cohen; Robert A. Huber; Michael Jankowski; Melvin John; Jan Menzner; et al. (Politische Vierteljahresschrift, 2022)
The GLES Open Science Challenge 2021 was a~pilot project aimed at demonstrating that registered reports are an appropriate and beneficial publication format in quantitative political science that helps to increase transparency and replicability in the research process and thus yields substantial and relevant contributions to our discipline. The project resulted in the publication of this special issue, which includes seven registered reports based on data from the German Longitudinal Election Study (GLES) collected in the context of the 2021 German federal election. This concluding article of the special issue brings together the perspectives of the participating authors, reviewers, organizers, and editors in order to take stock of the different experiences gained and lessons learned in the course of the project. We are confident that future projects of a~similar nature in political science, as well as authors, reviewers, and editors of registered reports, will benefit from these reflections.
Keywords: 320; Registered reports; Open science; Quantitative political science; Electoral research; 2021 German federal election; German Longitudinal Election Study; Quantitative Politikwissenschaft; Wahlforschung; Bundestagswahl 2021